2004
DOI: 10.1111/j.1399-0039.2004.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I serotypes and cytotoxic T‐lymphocyte responses among human immunodeficiency virus‐1‐uninfected Thai volunteers immunized with ALVAC‐HIV in combination with monomeric gp120 or oligomeric gp160 protein boosting

Abstract: Antigen-induced cellular immunogenicity may vary between populations due to differences in human leukocyte antigen (HLA) diversity and, hence, may play a critical role in the protection afforded by vaccines. In the setting of two, phase I/II human immunodeficiency virus-1 vaccine trials of a recombinant canarypox prime, and boosting with either recombinant monomeric gp120 or oligomeric gp160, we assessed the association between specific human leukocyte antigen (HLA) class I serotypes and the presence of cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…This was indicated by the fact that 61.1% of B*44-positive volunteers had HIV-specific CTL responses at a frequency that was higher than in other HLA serotypes (32). However, Novitsky et al reported that, at the level of the HLA supertype, a lower viral load was significantly associated with higher T cell responses to p24 for the A*02, A*24, B*27, and B*58 supertypes but not for the B*44 supertype in HIV-1 C subtype patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…This was indicated by the fact that 61.1% of B*44-positive volunteers had HIV-specific CTL responses at a frequency that was higher than in other HLA serotypes (32). However, Novitsky et al reported that, at the level of the HLA supertype, a lower viral load was significantly associated with higher T cell responses to p24 for the A*02, A*24, B*27, and B*58 supertypes but not for the B*44 supertype in HIV-1 C subtype patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…The HLA class I heavy chains encoded by these alleles differentially present highly conserved viral epitopes for cytotoxic T-lymphocyte (CTL) responses (5,29,39). Such HLA-restricted immune mechanisms provide clues for designing better vaccine antigens that can drive immune responses toward desirable epitopes, i.e., those are highly relevant to viral fitness (13,37,38,65,91).…”
mentioning
confidence: 99%
“…A number of HLA alleles have been found to be associated with HIV disease course; HLA B27, B57 and B58 have been associated with slower disease progression, whereas B18 and B35 have been associated with faster progression [28][29][30]. The small differences in the frequency of these HLA haplotypes between western and Thai populations do not appear to explain the decreased survival rates seen [31,32]. Heterozygosity for the CCR5 delta 32 mutation has been associated with decreased disease progression in Caucasian populations but is not present among Thai individuals.…”
Section: Discussionmentioning
confidence: 89%